The Customization of Science
XII, 209 p.
Keywords: This collection explores whether and how religious and secular worldviews and political ideologies held by scientists, citizens, decision-makers and politicians influence science as practiced and understood today. Contributors explore the social and scientific repercussions of 'customizing' science to fit the needs and interests of various groups.